REALITAS SOSIAL DALAM NOVEL RONGGENG DUKUH PARUK KARYA AHMAD TOHARI (Social Reality in Novel “Ronggeng Dukuh Paruk” by Ahmad Tohari) - Amriani H. (Balai Bahasa Sulawesi Selatan, 2014)
The objective of the writing is to describe social reality in Ronggeng Dukuh Paruk by Ahmad Tohari using sociology of literature theory. The data is analyzed using descriptive method, and collected by library study with identifying written data in novel Ronggeng Dukuh Paruk. The result shows that there is concerned social reality in Dukuh Paruk Subdistrict. It is caused by the poverty and lack of knowledge possessed by its society. Social reality found in the novel is poverty, sorcery, tyranny, love, prostitution, pre-wedding sex, trickery, social jealousy and sexual abuse.